Чайка: [комедия в двух действиях] / [художник А. Татарко] - Акунин Борис (Нева, 2002)
Книга-перевертыш Экземпляры: (20180411) / Инвентарный номер: 38514 / Цена: 34.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А44 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-64